Obinutuzumab plus CHOP is effective and has a tolerable safety profile in previously untreated, advanced diffuse large B-cell lymphoma: the phase II GATHER study. Issue 4 (21st March 2019) - Sharman, Jeff P.; Forero-Torres, Andres; Costa, Luciano J.; Flinn, Ian W.; Inhorn, Lowell; Kelly, Kevin; Bessudo, Alberto; Fayad, Luis E.; Kaminski, Mark S.; Evens, Andrew M.; Flowers, Christopher R.; Sahin, Deniz; et al.
Abstract: This study investigated the safety and efficacy of obinutuzumab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (G-CHOP) in patients with advanced diffuse large B-cell lymphoma (DLBCL) and explored the impact of cell-of-origin (COO) on patient outcomes. Patients ( N = 100) received obinutuzumab (1000 mg on the days 1, 8, and 15 of cycle 1, and day 1 of cycles 2–8) plus CHOP (cycles 1–6). For patients without grade ≥3 infusion-related reactions (IRRs) to standard-rate obinutuzumab infusion, a shorter duration of infusion (SDI) was evaluated. Overall and complete response rates, as determined according to the Cheson et al. criteria by investigators/independent radiological facility, were 82.0/75.0% and 55.0/58.0%, respectively. SDI of 120 minutes and 90 minutes were well tolerated with no grade ≥3 IRRs. Among all patients, IRRs typically occurred during cycle 1, day 1. G-CHOP is active and has an acceptable safety profile in the first-line treatment of patients with advanced DLBCL. Clinical Trials: NCT01414855DLBCL